Leading to the innovation in a public library / Nur Ain Abd Wahab - Abd Wahab, Nur Ain (2014)
Aims to explore the topic of leadership as perceived and practiced by public library leaders. Leadership happens at all levels. The leaders must manage strategically to enhance the awareness how beauty the environment of the library is in the public where they can fully maximize the library facilities to the fullest A project that has been organized lead to innovation may create new positive thoughts of Malaysian people.